Membangun Kinerja Pemasaran Melalui Orientasi Pasar, Inovasi Produk dan Kapabilitas Pemasaran - Nina Farliana; Indri Murniawaty; Choerul Hidayatti Munafitri (Sains: Jurnal Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of market orientation, product innovation, and marketing capabilities on marketing performance on stone craft craftsmen in Sedayu Village, Muntilan District, Magelang Regency. The population in this research is 90, with saturated samples techniques. This study uses a quantitative approach with data collection methods using questionnaires. The data analysis method used is descriptive analysis and multiple regression analysis through the SPSS Version 21 program. The results showed that market orientation, product innovation, marketing capability have a significant positive effect on marketing performance, either partially or simultaneously. Variables of market orientation, product innovation, and marketing capabilities simultaneously affected marketing performance by 47.4%. While partially market orientation had the greatest influence on marketing performance by 14.30%, product innovation had an effect of 5.10%, and marketing capabilities had an effect on marketing performance by 6.20%.